AI’s Impact on Students’ Oral Presentation Skills: Indonesian Lecturers’ Pedagogical Responses - Primandhika, Restu Bias; Solihati, Nani; Zulaiha, Siti (Edukasi, 2026)
This study investigates lecturers’ pedagogical responses to student challenges in processing information for oral presentation skills in the era of artificial intelligence. Employing a qualitative case study design with thematic analysis, the study involved eight lecturers and 62 students from three private universities in Cimahi, Indonesia. Data were collected through in-depth interviews and Focus Group Discussions (FGDs) and analysed using Braun and Clarke’s six-phase thematic framework. The findings reveal that 1) all lecturer participants (100%) reported an erosion of students’ oral communication skills, manifested in a gap between high-quality visual artifacts and weak verbal performance, deficits in spontaneous responses, and degradation of non-verbal communication, indicating the role of artificial intelligence as a cognitive crutch, 2) lecturers responded to these challenges by diversifying pedagogical strategies, particularly through explicit AI usage policies (100%), intensified oral validation via spontaneous question-and-answer sessions (87.5%), and process-oriented assessment (75%), and 3) student responses were ambivalent, with the majority (77.4%) perceiving the new assessment approaches as fairer and more transparent, while a minority (22.6%) expressed resistance related to performance anxiety. These findings suggest that the most effective response to AI-related challenges is not the prohibition of technology, but a pedagogical redesign that prioritizes process validation, human interaction, and assessment security to maintain rigorous academic standards in Indonesian higher education.